Effect of Tensile Reinforcement Ratio on the Effective Moment of Inertia of Reinforced Lightweight Concrete Beams for Short Term Deflection Calculation - Akmaluddin, Akmaluddin (Journal of Engineering and Technological Sciences, 2011)
This paper presents an improvement model of the effective moment of inertia  to  predict  the  short  term  deflection  of  reinforced  lightweight  concrete beam.  The  models  were  developed  using  9  beams  of  reinforced  pumicelightweight concrete tested under two symmetrical-point loads. The presence of steel  reinforcement  in  the  beam  was  taken  into  consideration  in  the  developed model.  The  models  were  verified  by  test  carried  out  on  other  9  beams.  Those beams subjected to various-point loads and compressive strength. The results of investigation revealed that crack moment of inertia increased with the increased tensile reinforcement ratio. Thus, the reinforcement ratio significantly affects the value of effective moment of inertia of reinforced lightweight concrete beam. All the  beam  test  results  produced  considerable  deflection  in  comparison  to  that obtained  using  current  Codes  either  ACI  or  SNI.  The  proposed  model demonstrated  a  good  agreement  to  the  experimental  results  and  in  some  cases have similar trend to that of the ACI or SNI prediction.